In vitro antiviral activity of aqueous extracts of polygonum minus huds leaves against herpes simplex virus 1 - Shahar, Saleha (2015)
Polygonum minus (P. minusi extract was investigated as a potential antiviral agent against herpes simplex virus I (HSY- I). Cell survival to assess antiviral activity was detrmined via MTT and crystal violet assays. Initially, cytotoxicity for minimal non-toxic dose was determined prior to MIT assay. The HSY-l was infected at 1.00 MOl into Vero cells and the cytopathic effect was observed by inverted microscopy. Antiviral treatment was performed based on a time-of-addition routine; simultaneous-treatment, pre-treatment and post-treatment for 24 hours incubation. Aqueous extract was found to be effective in inhibiting HSY-I in post-treatment, mildly effective in pre-treatment and not effective in simultaneous treatment. In conclusion, aqueous extract of P. minus could be a potential candidate for anti-HSV-I activity. Indeed, further studies are required before a conclusive experimental finding be suggested.